Production of High Amounts of Hepatotoxin Nodularin and New Protease Inhibitors Pseudospumigins by the Brazilian Benthic Nostoc sp. CENA543 - Jokela, Jouni; Heinilä, Lassi M. P.; Shishido, Tânia K.; Wahlsten, Matti; Fewer, David P.; Fiore, Marli F.; Wang, Hao; Haapaniemi, Esa; Permi, Perttu; Sivonen, Kaarina (Frontiers in Microbiology, 2017)
Nostoc is cyanobacterial genus, common in soils and a prolific producer of natural products. This research project aimed to explore Brazilian cyanobacteria for new bioactive compounds and their characterization. Here we report the production of hepatotoxins and new protease inhibitors from benthic Nostoc sp. CENA543 isolated from small, shallow, saline-alkaline lake in the Nhecolândia, Pantanal wetland area in Brazil. Nostoc sp. CENA543 produces exceptionally high amounts of nodularin-R. This is the first free-living Nostoc found that produce nodularin at comparable levels as the toxic, bloom-forming, Nodularia spumigena. We also found and characterized pseudospumigins A-F, which are a novel family of linear tetrapeptides. Pseudospumigins are structurally related to linear tetrapeptide spumigins and aeruginosins both present in N. spumigena but differ in respect to their diagnostic amino acid which is Ile/Leu/Val in pseudospumigins, Pro/mPro in spumigins and Choi in aeruginosins. The pseudospumigin gene cluster is more similar to the spumigin biosynthetic gene cluster than the aeruginosin gene cluster. Pseudospumigin A inhibited trypsin (IC50 4.5 μM after 1 h) in a similar manner as spumigin E from N. spumigena but was almost two orders of magnitude less potent. This study identifies another location and environment where the hepatotoxic nodularin has the potential to cause deaths of eukaryotic organisms.